THE EFFECT OF SELF-MANAGEMENT ON STUDENT LEARNING DISCIPLINE AT SMAN 13 MAKASSAR - Shilsila Nurfadilah Asmi; Abdullah Pandang; Sahril Buchori (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to examine the effect of implementing self-management techniques on student learning discipline at SMAN 13 Makassar. The background of this research lies in the importance of learning discipline for academic success and how self-management techniques can serve as an effective tool to cultivate discipline. The research method used is a quasi-experiment with two groups: an experimental group receiving self-management intervention and a control group. Data were collected through questionnaires, observations, and interviews, and then analyzed descriptively and statistically using t-tests. The results of the study indicate a significant improvement in students’ learning discipline after implementing self-management techniques. Before the intervention, 60% of students were in the low discipline category and 40% in the high category. After applying self-management techniques, 70% of students fell into the high discipline category. A p-value of < 0.05 indicates a significant difference between the experimental and control groups. These findings are supported by observations and interviews showing that self-management techniques enhance student participation, time management, and learning motivation. In conclusion, self-management techniques are effective in improving learning discipline and should be integrated into school counseling programs.